(untitled) (Research, Society and Development, 2026)
The adoption of measures that promote surgical safety is essential to prevent adverse events and improve clinical outcomes in pediatric patients. Thus, this review aims to analyze the scientific evidence on the use of innovative strategies related to pediatric surgical patient safety for the prevention of adverse events. This study analyzed scientific evidence on strategies aimed at ensuring the safety of pediatric surgical patients, with an emphasis on preventing adverse events. It is an integrative review conducted in the LILACS, PubMed, Scopus, and Web of Science databases. A total of 2,088 studies were identified; after applying exclusion criteria, 13 were included. Surgical checklists were the most commonly used tools. Innovations included process analysis, emergency protocols, error reporting, interviews, record reviews, adapted toys, and furniture. The engagement of children and their parents in the safety verification process was also highlighted. The implementation of these strategies showed proven benefits. However, adherence by professionals to completing checklists and by parents to the proposed actions remains a challenge, making it necessary to adopt measures that enhance participation.